Existência de solução para um problema elíptico envolvendo o expoente crítico de Sobolev - Böck, Lisiane Daniela (2020)
This work presents a study on the existence or not of a solution for the following elliptical problem with Sobolev’s critical exponent 8> ><>>: u = u2 1 + f(x; u) in u > 0 in u = 0 on @ ; where is a limited domain in Rn, n 3, 2 = 2n n 2 and f adequate.